DETERMINATION OF OIL AND FAT LEVELS IN LIQUID WASTE OF PALM OIL INDUSTRY IN MUARO JAMBI DISTRICT - Rahmi, Rahmi (ALKIMIA, 2021)
Waste contains pollutants that can change the quality of the environment.Wastewater discharged into the environment must comply with standard quality standards. One of the parameters that are harmful to the environment are oils and fats. Oils and fats are on the surface of the water so they can block sunlight from entering the water and can interfere with the activities of aquatic biota. Determination of oil and fat content in palm oil industrial wastewater in Muaro Jambi District using the gravimetric method based on the Indonesian National Standard 6989.10:2011. The results obtained in the inlet waste pond of PT. A, PT. B and PT. C respectively 582.4 mg/L; 380.2 mg/L and 221.4 mg/L while for PT. A, PT. B and PT. C respectively 78.8 mg/L; 53.6 mg/L and 12.8 mg/L. According to the Regulation of the Minister of the Environment of the Republic of Indonesia No. 5 of 2014, the maximum permissible level for liquid waste oil and fat at the outlet liquid waste of the palm oil mill industry is 25 mg/L. Based on the test results, it can be concluded that the levels of oil and fat that meet the quality standards of palm oil liquid waste are outlet waste from PT. C.